Dynamically reversible cooperation and interaction of multiple rotating micromotors. Issue 7 (7th March 2023) - Zhu, Shilu; Cheng, Yifan; Chen, Jialong; Liu, Guangli; Luo, Tingting; Yang, Runhuai
Abstract : A microsystem composed of multiple rotating micromotors can achieve reversible transformation between cooperative and interactive modes, and dynamic behaviours of self-organization are realized based on the microsystem. Abstract : Micromotors have been shown to have great potential in various fields ( e.g., targeted therapeutics, self-organizing systems), and research on the cooperative and interactive behaviours of multiple micromotors could potentially revolutionize many fields in terms of performing multiple or complex tasks to compensate for the limitations of individual micromotors; however, dynamically reversible transitions among diverse behaviours remain much less explored, and such dynamic transformations are advantageous for achieving complex tasks. Here, we present a microsystem consisting of multiple disk-like micromotors capable of performing reversible transformations between cooperative and interactive behaviours at the liquid surface. The micromotors with aligned magnetic particles in our system have great magnet properties, which provides a strong magnetic interaction with each other and is vital for the whole microsystem. We offer and analyse the physical models among multiple micromotors concerning the cooperative and interactive modes in the lower and higher frequency ranges, respectively, between which the state transformation can reversibly occur. Furthermore, based on the proposed reversible microsystem, the feasibility of the application of self-organization is verified by demonstrating three different dynamic self-organizing behaviours. Our proposed dynamically reversible system has great potential to serve as a paradigm for studying cooperative and interactive behaviours among multiple micromotors in the future.